The impacts of different eyes, individual differences, and different time points in healthy rats on the variability of visual electrophysiological examination indicators - Chen, Hong; Cheng, Yu; Diao, Ke; Wang, YiFan; An, Jing; Zhang, Haijiang; Li, RongRong; Zhang, Dan; Cheng, SuMian; Zhang, Minglian; Wang, LiFei (Frontiers in Medicine, 2025)
PurposeThis article discussed the repeatability and coefficient of variation (CV) of flash visual evoked potential (FVEP) and full-field electroretinogram (ffERG) indicators of different eyes, individuals, and time points of normal male Sprague-Dawley rats, providing a reference for selecting a reasonable control scheme for retinal and optic nerve disease rat models.MethodsTwenty normal 6-8 week Sprague-Dawley rats were selected, from which 10 randomly chosen rats underwent ffERG examination and the other 10 underwent FVEP examination. At different time points (1 d, 7 d), Roland visual electrophysiological device was utilized to record in FVEP P2 peak time and N2-P2 amplitude, peak time and amplitude of dark-adapted 0.01 ERG b-wave, peak time and amplitude of dark-adapted 3.0 ERG a- and b-waves, OPs OS2 amplitude, peak time and amplitude of light-adapted 3.0 ERG a- and b-waves, and N1-P1 amplitude of light-adapted 3.0 flash ERG. Meanwhile, we also analyzed the mean ± standard deviation, range, and CV, as well as compared mean ± standard deviation, range, and CV values between two eyes of the same rat and monocular results before and after intervention.ResultsStable waveforms could be recorded for each rat. Among them, the smallest CV was obtained at the peak time of the FVEP P2 wave (10.1%), while that of amplitude in the VEP P2 wave was relatively large (41.2%). In the ffERG examination, the CV value at each peak time was relatively small (12.9% -39.8%), while the CV value for each wave amplitude was relatively large (33.4% -93.5%). In each waveform, the lower the amplitude, the greater the CV value. By comparing the three control schemes, the CV at the P2 peak time of FVEP examination generated using the baseline ratio approach was the smallest, and that of amplitude calculated using the absolute value approach was the smallest. In the ffERG examination, except for the light-adapted 3.0 ERG a-wave with the lowest CV obtained by the baseline ratio method (57.7%), the CV values of the other examination items were as follows: OD/OS ratio method<absolute value method<baseline ratio method. The CV at each peak time generated by the baseline ratio method was the highest.ConclusionIn normal adult male Sprague-Dawley rats, the optic nerve function assessment at P2 wave peak time in FVEP is the most stable, and the CV of N2-P2 amplitude is relatively large. During retinal function assessment by ffERG, the detection error for different eyes of the same individual<different individuals<different time points, which can be reduced using a reasonable control scheme.